Estudo de sorbicilinoides e outros metabólitos de Penicillium chrysogenum isolado de Gustavia sp. - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Penicillium chrysogenum is a filamentous fungus, found in several habitats, including inside to plant cells, as endophytic fungus. This species is well known for the production of β-lactam antibiotics, such as penicillin and its derivatives, which are of great importance for the pharmaceutical industries, as well as producing crisogin, roquerfortina and sorbicillinoids. Sorbicillinoids are mostly reported as dimers, called bisorbicilinoids, and are considered as a class of substances with very accentuated bioactive properties, such as: cytotoxic, antiviral, antimicrobial, antioxidant, among others. In order to further study the extracts from the liquid medium of P. chrysogenum strain 401, isolated Gustavia sp., which produced bisorbicillinoids (trichodimerol, dihydrotrichodimerol and tetrahydrotrichodimerol), in this work were isolated by chromatographic techniques in addition to the aforementioned metabolites, other metabolites belonging to this class such as 2',3'-dihydrosorbicillin monomer and the tetrahydrotrichodimer ether dimer, this late reported for the first time in the genus Penicillium, the alkaloid chrysogine and N-(2-hydroxypropanoyl)-2-aminobenzoic acide amide, all identified by spectrometric and spectroscopic techniques and confirmed by comparison with literature data. All the isolated substances were submitted for the first time to the anti-glycation assay. Among the isolated main compounds are the bisorbicillinoids tetrahydrotrichodimer ether, trichodimerol, tetrahydrotrichodimerol, and the 2',3'-dihydrosorbicillin monomer, which exhibited excellent to moderate anti-glycation, inhibiting the formation of advanced glycation end products (AGEs) by the two systems tested glyoxal / BSA and fructose / BSA.
Keywords: Penicillium; Fungos; CIENCIAS EXATAS E DA TERRA: QUIMICA: QUIMICA ORGANICA: QUIMICA DOS PRODUTOS NATURAIS; Penicillium chrysogenum; Sorbicilinoides; Atividade antiglicação; Éter tetrahidrotricodímero